2022
DOI: 10.1186/s12879-022-07413-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical presentation across two waves of COVID-19: a retrospective cohort study

Abstract: Background Only a few studies have performed comprehensive comparisons between hospitalized patients from different waves of COVID-19. Thus, we aimed to compare the clinical characteristics and laboratory data of patients admitted to the western part of Denmark during the first and second waves of COVID-19 in 2020. Furthermore, we aimed to identify risk factors for critical COVID-19 disease and to describe the available information on the sources of infection. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
6
22
2
4
Order By: Relevance
“…In contrast, patients admitted during the first surge presented with lower oxygen saturation and higher temperature compared to surge 2 on admission according to Buttenshon et al study. However, similar to our reports they presented with lower SBP during surge one [ 17 ]. The SARS-CoV-2 virus can infect various organs using angiotensin-converting enzyme (ACE2) receptors to enter cells [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, patients admitted during the first surge presented with lower oxygen saturation and higher temperature compared to surge 2 on admission according to Buttenshon et al study. However, similar to our reports they presented with lower SBP during surge one [ 17 ]. The SARS-CoV-2 virus can infect various organs using angiotensin-converting enzyme (ACE2) receptors to enter cells [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Underlying diseases are associated with a higher risk of severe COVID-19 and its complications [ 15 , 16 ]. In a study comparing two surges of COVID-19 pandemic showed that more than 80% of patients had at least one comorbidity with hypertension being the most common comorbidity similar to our results [ 17 ]. Vahidy et al reported that the number of COVID-19 hospitalized patients with hypertension was significantly higher during surge 1 of the COVID-19 pandemic in Houston, which is in alignment with our results [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 23 , 24 , 25 However, reviewing our data patients with more severe disease requiring hospital admission, these patients were older, with greater underlying comorbidity and frailty, and higher concentrations of markers of disease activity; CRP, ferritin, and NT‐proBNP, in keeping with other studies in nondialysis and dialysis patients. 26 , 27 , 28 , 29 We found that patients requiring acute hospital admission had marginally lower, but not significantly lower 25ViD levels, but had received similar dosages of alfacalcidol, but alfacalcidol dosages were lower in those who died with COVID‐19. However, on multivariate testing only comorbidity, and markers of inflammation; CRP and NT‐proBNP remained significantly associated with disease severity requiring hospital admission, similar to observational reports from nondialysis patients.…”
Section: Discussionmentioning
confidence: 71%
“…However, on multivariate testing only comorbidity, and markers of inflammation; CRP and NT‐proBNP remained significantly associated with disease severity requiring hospital admission, similar to observational reports from nondialysis patients. 26 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%